1997
DOI: 10.1051/apido:19970612
|View full text |Cite
|
Sign up to set email alerts
|

A scientific note on oxalic acid by topical application for the control of varroosis

Abstract: oxalic acid / varroosis / honeybee / honey / residues Tests on the use of oxalic acid for controlling varroosis (Takeuchi et al, 1983; Zjuman, 1987;Radetzki et al, 1994;Nanetti et al, 1995;Imdorf et al, 1997) Bee mortality was determined using 'underbasket traps' applied to each hive (Accorti, 1994).The mean efficacy of the three treatments with oxalic acid was 95% (± 7.39%) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…In one case, even the highest concentration (7% oxalic acid dihydrate, 25-30 mL per hive) did not raise the oxalic acid content of the honey directly after treatment (Mutinelli et al, 1997).…”
Section: Tricklingmentioning
confidence: 88%
See 3 more Smart Citations
“…In one case, even the highest concentration (7% oxalic acid dihydrate, 25-30 mL per hive) did not raise the oxalic acid content of the honey directly after treatment (Mutinelli et al, 1997).…”
Section: Tricklingmentioning
confidence: 88%
“…Repeated treatments with a high concentration (6 and 7%) did not increase the efficacy (Mutinelli et al, 1997); one study even described a reduced mite mortality of 56.2% (Baggio and Mutinelli, 2003b). Mutinelli and Baggio (2002) applied Ipereat, a ready mixed solution containing about 4.2% oxalic acid dihydrate, ethereal oils, propolis and sugar and reported efficacies up to 93.9%.…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the first two methods were better than cellulose strips. Mutinelli et al (16) found the efficacy of sprayed 5% (w/v) oxalic acid to be higher than that of a topical application. Rashid et al (10) applied oxalic acid in sugar syrup at 4.2%, 3.2%, and 2.1%, and similar work was done using 2.9% oxalic acid (17).…”
Section: Introductionmentioning
confidence: 99%